A validity- and kinematics-aware approach for optimizing fabrication orientation. (April 2023) - Pan, Wanbin; Zhang, Xinying; Wang, Shufang; Lu, Wen Feng; Wang, Yigang
Abstract: Ensuring the removability of support structure and improving the surface quality of assembly interface are two key requirements to guarantee a model a valid fabrication and promote its kinematic performance in a product. Generally, determining a suitable fabrication orientation for the model is an effective way to meet those requirements. Accordingly, a novel validity- and kinematics-aware approach for optimizing fabrication orientation is proposed in this work. Viewing that it is effective and efficient (in an optimizing process) to evaluate whether a fabrication orientation will take unremovable support structures to a model by checking whether they contact the model on its inaccessible surface regions, a new voxel-based surface-accessibility analysis method is proposed. In detail, to analyze the accessibility (by a cleaning tool) of each surface region accurately, the input model and its bounding box are voxelized together first and represented by using a new voxel-adjacency graph. Then, integrating rapid individual-single-accessibility analysis, voxel-layer-scan analysis, and accessible direction reuse, a parallelable variable-neighborhood-search method is put forward based on the above graph. With this method, all inaccessible surface regions (if any) of the model can be effectively and efficiently identified at once. Moreover, the above-mentioned key requirements are usually two conflicting goals (especially for a model having two or more assembly interfaces) in determining suitable fabrication orientations. To make those goals reconcile with each other, a multi-objective optimization problem is first formulated to explore a set of pareto-optimized fabrication orientations. Here, two new functions are elaborately designed to evaluate the removability of support structures (by counting the number of inaccessible surface regions that appear support structures) and the surface quality of assembly interfaces, respectively. Finally, a greedy method is adopted to recommend one from these compromising fabrication orientations to the uses as the best-suitable fabrication orientation. Experiments are presented to demonstrate the characteristics, effectiveness, and efficiency of the approach. The methodological comparisons also show that the approach has several advantages in AM applications where support structures are mainly removed manually and the models are fabricated for mechanisms. Highlights: Optimizing fabrication orientation by reconciling validity with kinematics. Smart and efficient accessible analysis by parallelable variable neighborhood search. Rapid finding accessible surface regions by voxel-layer scan in voxel-adjacency graph.